2015
DOI: 10.1007/s00787-015-0760-y
|View full text |Cite
|
Sign up to set email alerts
|

Life adversities and suicidal behavior in young individuals: a systematic review

Abstract: Suicidal behavior in young people is a significant public health problem. However, it is not yet clear whether adversities (adverse life events) may be related to suicidality in adolescence and early adulthood. This paper aimed to investigate systematically the association between the type/number of adverse life events and experiences and suicidal behavior in young people. We developed a detailed strategy to search relevant articles in Pubmed, Scopus, PsycInfo, and Science Direct (January 1980-January 2015) ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
100
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(120 citation statements)
references
References 67 publications
13
100
1
6
Order By: Relevance
“…In addition, as in the original scale, the existence of a high relationship between cyber-victimization and depressive symptomatology can be observed. This result supports the large number of studies that show the negative consequences of victimization on the wellbeing and adjustment of the victim (Garaigordobil 2017;Navarro et al 2018;Serafini et al 2015;Yubero et al 2017). In this victimization situation, the family plays an essential role in helping their child to get out of this situation (Garaigordobil and Machimbarrena 2017;Navarro et al 2015;Nocentini et al 2018).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, as in the original scale, the existence of a high relationship between cyber-victimization and depressive symptomatology can be observed. This result supports the large number of studies that show the negative consequences of victimization on the wellbeing and adjustment of the victim (Garaigordobil 2017;Navarro et al 2018;Serafini et al 2015;Yubero et al 2017). In this victimization situation, the family plays an essential role in helping their child to get out of this situation (Garaigordobil and Machimbarrena 2017;Navarro et al 2015;Nocentini et al 2018).…”
Section: Discussionsupporting
confidence: 78%
“…In addition, unlike traditional victimization, parents frequently do not know about the victimization experienced by their child, which increases the victim's feeling of loneliness Nocentini et al 2018). Thus, authors such as Thompson et al (2012) suggest that the accumulation of adverse life events (cumulative lifetime adversities) in adolescence is closely related to suicidal ideation (see Serafini et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…8,86 More specifically, youth who feel connected and committed to school are at a lower risk of harming others through dating violence, 29,76 youth violence, 20,82,87–89 sexual violence, 28 and bullying, 72 and are at lower risk for suicide, 89,90 and strong family support and connectedness can be protective against perpetration of child abuse and neglect, 91–93 teen dating violence, 29 youth violence, 8,94,95 bullying, 96 and suicide. 65,97–100 Also, youths’ association with prosocial peers has been shown to be protective against perpetration of teen dating violence, 101 youth violence, 20 bullying, 81 and suicide. 102 …”
Section: Risk and Protective Factors Across The Social Ecology*mentioning
confidence: 99%
“…Moreover, although various studies have shown the impact of self-blame and shame on the symptomatology of CSA victims, more precisely on PTSD and depressive symptoms, we know little about their impact on suicidal ideation and attempts. According to a recent review, sexual abuse is the adverse life event most consistently and strongly associated with suicide among young people aged 10-25 years (Serafini et al, 2015). Suicide is the first worldwide cause of death among adolescent girls aged 15-19 years (Patton et al, 2009).…”
mentioning
confidence: 99%